AB0292 Biomarkers That Might Help to PREDICT Sustained Remission in Rheumatoid Arthritis. (10th June 2014) - Yilmaz-Oner, S.; Can, M.; Ozen, G.; Atagunduz, P.; Direskeneli, H.; Inanc, N.
Abstract : Objectives: The treatment target of rheumatoid arthritis (RA) is to suppress the inflammation as much as optimally possible and to induce remission. In this study, we have intended to find biomarkers which support and might help to predict sustained remission via measuring serum Calprotectin, IL-6, Helix II, ICTP, MMP-3, resistin and leptin levels of patients in DAS28 remission. Methods: Serum levels of Calprotectin, IL-6, Helix II, ICTP, MMP-3, resistin and leptin were measured by ELISA in 80 patients (F/M:54/26, mean age: 51.4±12.0 year, mean disease duration: 11.4±8.0 year, 68.7% [n=55] RF positive, 60.7% [n=48] anti-CCP positive) whom were in DAS28-ESR remission. The patients were evaluated once again at a 2nd visit after six months to detect whether they are in remission or not. Additionally, 80 controls who do not have any rheumatic disease and compatible with patients in terms of age, gender and comorbidities were also included to the study. Patients in new ACR/EULAR remission, Boolean based remission and remission according to SDAI, were determined. Results: At baseline evaluation (1st visit), 33 patients (41.2%) were in Boolean remission, 39 (48.7%) patients were in SDAI remission. At the 2nd visit, 51 (63.8%) patients were in DAS28, 22 (27.5%) were in Boolean and 34 (42.5%) patients were in SDAI remission. In the study group, mean serum MMP-3, ICTP, resistin and IL-6 levels were statistically significantly higher than the controls. Patients in Boolean and SDAI remission at their 1st visit, also had significantly higher serum ICTP, resistin and IL-6 levels in comparison with the controls. Patients in Boolean remission at the 1st and 2nd visits had higher ICTP levels (p=0.001), in DAS28 remission had higher MMP-3 (p=0.022), ICTP (p=0.000), resistin (p=0.001), IL-6 (p=0.000) levels and in SDAI remission had higher ICTP (p=0.000), resistin (p=0.028) and IL-6 (p=0.025) levels in comparison to controls. Although at the 1st visit, there wasn't a significant difference between mean serum biomarker levels of patients in Boolean remission than the ones in non-remission, SDAI non-remission patients had significantly higher serum IL-6 levels than the patients in SDAI remission. The difference between serum biomarker levels of patients in DAS28 and in SDAI remission at the 1st and 2nd visits with the patients who were in remission at the 1st, but not at the 2nd visit was non-significant. When we compared serum biomarker levels of patients in Boolean remission at the 1st and 2nd visits with patients that were in remission at the 1st visit, but not at the 2nd, we observed that MMP-3 levels were higher in patients that were in non-remission at the 2nd visit (20540.5±13084 vs 40567.8±27826.9 pg/ml; p=0.04). Conclusions: New remission criteria could determine patients with more suppressed inflammation and less risk of developing joint damage, but it is not possible to say that the relapse risk is eliminated completely. Some of the biomarkers, like MMP-3 might also have a predictive value for the relapse in patients with RA. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4153